2012
DOI: 10.1371/journal.pone.0032296
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Preconditioning in the Animal Kidney, a Systematic Review and Meta-Analysis

Abstract: Ischemic preconditioning (IPC) is a potent renoprotective strategy which has not yet been translated successfully into clinical practice, in spite of promising results in animal studies. We performed a unique systematic review and meta-analysis of animal studies to identify factors modifying IPC efficacy in renal ischemia/reperfusion injury (IRI), in order to enhance the design of future (clinical) studies. An electronic literature search for animal studies on IPC in renal IRI yielded fifty-eight studies which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
158
1
10

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(173 citation statements)
references
References 35 publications
(30 reference statements)
4
158
1
10
Order By: Relevance
“…62 IPC-associated protective effects were reported for all three parameters. Interestingly, renoprotection was not evident in the female subgroup, stressing the need for future studies in female subjects.…”
Section: Animal Studiesmentioning
confidence: 88%
“…62 IPC-associated protective effects were reported for all three parameters. Interestingly, renoprotection was not evident in the female subgroup, stressing the need for future studies in female subjects.…”
Section: Animal Studiesmentioning
confidence: 88%
“…Free radical production is one of the most important mechanisms of tissue ischemia-reperfusion injury 11 , low-energy shock waves pretreatment can reduce the renal oxidative stress caused by high-energy shock wave lithotripsy 19 . From this study, 24 hours after reperfusion, serum iNOS and renal tissue MDA levels in the LESP+IR group were both significantly lower than those of the IR group, indicating that low-energy shock pretreatment can reduce free radicals induced by ischemia and reperfusion in a short time.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Ischemic preconditioning (IPC) is a potent protective strategy in which a brief occlusion of ischemia and reperfusion results in tolerance to subsequent ischemia-reperfusion injury 8,9 . It has been demonstrated in multiple tissues and organs including the heart, liver, small intestine, and renal tissues [10][11][12][13] . Low-energy shock waves have been used in many fields to reduce the damage induced by tissue ischemia or to improve recovery after ischemia.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several IPC methods have been described, including having the stimulus localized at the target organ or remotely from it, having 1 continuous episode of ischemia or several cycles of brief ischemia and reperfusion, and varying the interval between the IPC stimulus and the index ischemia. [1][2][3] A recent systematic review and meta-analysis 2 concluded that, overall, IPC reduces histologic damage and serum creatinine levels; however, some studies reported that IPC does not result in any protection at all. 4,5 Most IPC investigations in kidneys have used an adult male rat as the animal model and a 40-or 45-minute IPC and IRI period.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent meta-analysis showed that most regimens have used localized IPC. 2 Of particular note, a continuous regimen of 15 minutes of IPC before injury has been shown to result in histologic and functional protection. 1 MicroRNAs (miRNAs) are a large family of endogenous, small non-coding RNAs that are thought to regulate the expression of the majority of human protein-coding genes.…”
Section: Introductionmentioning
confidence: 99%